Kloning Gen Cry Dari Bacillus Thuringiensis Var. Kurstaki = Cloning Of The Cry Gene From Bacillus Thuringiensis Var. Kurstaki - Perpustakaan UGM, i-lib ([Yogyakarta] : Jurusan Sejarah Fak. Ilmu Budaya dan Program Studi Sejarah Program Pasca Sarjana UGM, 1998)
Bacillus thuringiensis is an entomopathogenic organism. The pathogenic effect is caused by crystalline protein, 5-endotoxin, which is encoded by the cry gene. The aim of this study was to clone the cry gene from B. thuringiensis var. kurstaki with a genomic library approach. Hindi-11 digested B.thuringiensis total DNA was ligated to Hind!!! digested of pUC19, and then used to transform Escherichia coli DH5a. Selection of transformans carrying recombinant was done by a-complementation and a recombinant clone containing the cry gene was further screened by non-radioactive hybridization method using a probe synthesized from the conserved region of the published cry genes. The result suggested that two recombinant clones with the insert size of 3.4 kb and 2.0 kb, respectively, carrying the cry gene.